Effect of concurrent application of heat, swim stress and repeated dermal application of chlorpyrifos on the hippocampal neurons in mice - Mitra, Nilesh K.; Nadarajah, Vishna D.; Siong, How Hee (Folia Neuropathologica, 2009)
Dermal absorption of chlorpyrifos (CPF), an organophosphate (OP) pesticide, is important because of its popular use. Stress has been reported to exacerbate neurotoxic effects of certain OP pesticides; however, quantitative studies to corroborate this are not reported. This study correlates the changes in acetylcholinesterase (AChE) levels and neuronal counts in areas of the hippocampus to consecutive exposure of stress, heat and CPF. Male mice (60 days) were segregated into six groups: one control, one stress control, and four treated groups (n=10). CPF was applied in doses of 1/2 and 1/5 of dermal LD50 (E1 and E2) over the tail of mice under occlusive bandages for 3 weeks. Stress control [(s) C] mice were subjected to swim stress at 38°C (6 mins/day, 3 weeks). (s) E1 and (s) E2 were subjected to swim stress before CPF application. Blood and brain AChE levels were estimated using a spectrofluorometric method (Amplex Red). Pyramidal neurons of the cornu ammonis of the hippocampus under Nissl stain from histological sections were counted per unit area of section and analyzed statistically using one way ANOVA. Swim stress at 38°C aggravated reduction of serum AChE by dermal exposure to CPF by 19.7%. Neurons of CA3 and CA1 regions of the hippocampus showed significant reduction in neuronal counts in (s) E1 and (s) E2 groups compared to E1 and E2 groups. Whereas application of CPF 1/2 dermal LD50 (E1) showed significant reduction of neuronal counts only in the CA3 area.